Monograph of Nylanderia (Hymenoptera: Formicidae) of the World, Part II: Nylanderia in the Nearctic - Kallal, Robert J.; Lapolla, John S. (Zootaxa, 2012)
The taxonomy of the Nearctic Nylanderia fauna is revised. Three new species are established, bringing the total numberof native species from the region to 14. The new species are: N. magnella, N. querna, and N. trageri. Several speciespossess workers that are difficult to distinguish from each other and the presence of males is required for morphologicalidentification. This is particularly the case with N. vividula and N. terricola. Two subspecies are synonymized: N. vividulamjobergi is considered a junior synonym of N. vividula and N. vividula antillana is considered a junior synonym of N.guatemalensis. At least five Nylanderia species have been introduced to the Nearctic region, including: N. bourbonica,N. flavipes, N. fulva, N. pubens, and N. steinheili. Another species, N. guatemalensis, is also included because its widedistribution across the Caribbean and Central America suggest it could become introduced to the Nearctic region. Iden-tification keys are provided for the workers of native and introduced species and the males of native species. Distributionmaps are provided for native and introduced species. Photomontage images are provided for the worker of each introduced species and all castes of the native species.